Precision medicine for prostate cancer. Issue 11 (November 2014) - Galazi, Myria; Rodriguez-Vida, Alejo; Ng, Tony; Mason, Malcolm; Chowdhury, Simon
<x xml:space="preserve">Abstract</x> Metastatic castration-resistant prostate cancer remains a lethal disease despite considerable progress in systemic therapy over the past decade. The recent advances in genomic sequencing have improved the molecular classification of prostate cancer. The translation of genomic data into clinically relevant prognostic and predictive biomarkers to guide therapy is still in its infancy and therapies for castration-resistant prostate cancer are still used empirically. We discuss these genomic aberrations in more detail, focusing on androgen receptor signaling, ETS transcription factor gene rearrangements and PTEN loss. The incorporation of this genomic data within early phase clinical trials is evolving and may prove significant in advancing personalized care in prostate cancer.